Protein Interactions on Nano-Scale Controlled Surface - Kim, Hyo Jung; Ryu, Jae-Chun; Oh, Soon Jin (KOREAN BIOCHIP SOCIETY-KBCS, 2009)
In this study, antibody microarrays on a nano-scale controlled surface were prepared. Aspects of performance such as signal intensity, dependence of signal intensity on target antigen concentration, etc. were evaluated and compared with those of microarrays on amine, aldehyde, and epoxy surfaces. The signal intensities of the anti-TNIF-alpha antibody microarray fabricated on the nano-scale controlled surface were found to be 2-8 times higher than those prepared on the other surfaces. Additionally, the anti-TNF-alpha and anti-IL-1 beta antibody microarrays evidenced linear correlations between their signal intensities and concentrations of target antigen applied to the microarrays in a range between 3.0 nM-1.0 mu M. Furthermore, the antibody microarrays detected two different antigens simultaneously with similar signal intensity to those achieved in single antigen detection experiments.
Keywords: MICROARRAY TECHNOLOGY; DNA MICROARRAYS; THIN-FILMS; ARRAYS; IMMOBILIZATION; MICROCHIPS; PROSPECTS; BINDING; CHIPS; GOLD